Gellan gum based gastroretentive tablets for bioavailability enhancement of cilnidipine in human volunteers - Karemore, Megha N.; Bali, Nikhil R. (International journal of biological macromolecules, 2021)
Cilnidipine, a fourth-generation both L-and N-type calcium channel blocker (CCB) is safe and effective in lowering blood-pressure without reflex tachycardia compared to other dihydropyridine CCBs. However, its low solubility coupled with extensive first-pass metabolism results in very low oral bioavailability. Thus the study aimed to improve oral bioavailability of Cilnidipine by increasing its gastrointestinal transit-time and mucoadhesion. Gastroretentive tablets were prepared by direct-compression technique using gellan gum as hydrogel forming polymer and sodium bicarbonate as gas-generating agent. Statistical optimization was carried out by design approach which showed that gellan gum has significant impact on floating lag time, mucoadhesive strength, % drug release at 1 h and time to release 90% of drug. Drug release study revealed that optimized tablets prolonged drug release for 12 h and followed anomalous-diffusion indicating drug release is by coupling of both diffusion and erosion mechanism. Intragastric behaviour of formulation in human volunteers revealed that radio-opaque tablets remain buoyant in stomach for more than 6 h with sufficient mucoadhesion. Comparative pharmacokinetic profiling in human subjects revealed that relative bioavailability of Cilnidipine GR tablets was enhanced compared to reference tablets. Thus concluded that gastroretentive tablets to be promising strategy for improved oral bioavailability of Cilnidipine for effective treatment of hypertension. •Gellan gum & HPMC impart mucoadhesion; NaHCO3 aids in in-vivo buoyancy for >6 h.•Water diffusion, polymer swelling, hydrogel formation: leads to anomalous drug release.•Hydrophilic polymers enhance bioavailability, solubility & dissolution of cilnidipine.•Floating & mucoadhesion improve drug absorption in human volunteers.